First Report of Charcoal Rot Caused by Macrophomina phaseolina on Hemp ( Cannabis sativa ) in Missouri - Goodnight, Karen Morgan; Tian, Peng; Bissonnette, Kaitlyn M (Plant disease, 2023)
Charcoal rot, caused by , is abundantly present in the soil and has been reported as pathogenic to both soybean and corn, as well as numerous other hosts, including hemp grown for fiber, grain, and cannabinoids (Casano et al. 2018; Su et al. 2001). Hemp ( ) production in Missouri was a relatively new addition to the 2021 growing season. Charcoal rot was reported in Reynolds, Knox, and Boone counties in Missouri from commercial and experimental fields. One of the fields in question experienced heavy disease pressure and had an uneven stand loss, but the total loss was estimated at approximately 60% of the field and was attributed to charcoal rot. Charcoal rot signs and symptoms, microsclerotia on the lower stem and root tissue, wilting and stem discoloration, were observed on a majority of the hemp plants received at the University of Missouri Plant Diagnostic Clinic in July and late Fall of 2021, including samples from Bradford Research Farm in Boone County and Greenley Research Center in Knox County. Root and crown tissue from the hemp plants from the Greenley Research Center were cultured onto acidified potato dextrose agar (APDA). and other fungi grew from the plated tissue after about three days of incubation at room temperature. was confirmed based on the presence of melanized hyphae and microsclerotia (Siddique et al. 2021). The microsclerotia were black, round to ovoid shaped and ranged from about 34-87 µm (average 64 µm) in length and 32-134 µm (average 65 µm) in width (n = 44). A single-hyphae isolation from a putative isolate was conducted to obtain a pure culture. The culture from the Greenley Research Center was used to complete Koch's postulates of charcoal rot on four hemp cultivars. Sterilized toothpicks were added to pure cultures of on APDA and incubated at room temperature for one week to allow for colonization and for use in greenhouse inoculation. Four hemp cultivars (Katani, Grandi, CFX-2, and CRS-1) were grown in a sterilized silt loam for three weeks in a greenhouse. About four plants per cultivar were grown for inoculation and one plant per cultivar was used as a control. The plants were inoculated with the colonized toothpicks that were gently rubbed onto stem tissue and subsequently inserted into the soil at the stem. For six weeks, the plants were kept in greenhouse conditions of 25°C with a 12-hour light and dark cycle and were watered when soil appeared dry. Plants were kept in a loosely sealed container constructed from wood and vinyl sheeting to minimize cross contamination with other plants grown in the same greenhouse. Plants were monitored weekly for charcoal rot symptoms. Symptoms that resembled charcoal rot, wilting and microsclerotia on the lower stem, were present on inoculated plants after about four weeks and symptoms were not present on the control plants. Isolates resembling in culture were recovered from symptomatic plants; therefore, Koch's postulates were successfully fulfilled and the fungus was recovered from the inoculated plants. DNA was extracted from the pure cultures of both the initial isolate and the isolate obtained from Koch's postulates using GeneJet Plant Genomic DNA Purification Kit (Thermo Scientific, California, USA) and the internal transcribed spacer (ITS) region of ribosomal DNA including ITS1, 5.8S, and ITS4 regions were amplified using universal primers ITS1 and ITS4 (White et al. 1990). The ITS region was sequenced and compared to reference sequences in GenBank by BLAST analysis. Recovered isolates (GenBank accession no. OQ455934.1) showed closest sequence similarity (100%) to accession number GU046909.1. Little is known about the life cycle, growth conditions, and possible inoculum buildup in the soil in hemp in Missouri. In addition, is a known pathogen of corn and soybean and effective management strategies are challenging for these crops as well due to the broad host range of the pathogen. Cultural management practices, such as crop rotations to reduce inoculum in the soil and closely monitoring for symptoms, may help reduce the severity of this disease.